2015
DOI: 10.1007/s10637-015-0250-6
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of antigen with chemokine MCP-3 or MDC/CCL22 enhances DNA vaccine potency

Abstract: We evaluated the utility of chemokine MCP-3 and MDC/CCL22 as molecular adjuvants of DNA vaccines for botulinum neurotoxin serotype A (BoNT/A) in a Balb/c mouse model. Notably, the immunogenicity of the DNA vaccine against BoNT/A was not enhanced using a fusion of the AHc-C antigen with the MCP-3 or MDC/CCL22. Nevertheless, the potency of the DNA vaccine was significantly modulated and enhanced by co-administration of the AHc-C antigen with MCP-3 or MDC/CCL22. This strategy elicited high levels of humoral immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It has been reported that co-vaccination of antigens with cytokines is a novel and effective strategy to enhance immunization and regulate cellular and humoral immune responses to promote protective immunity against pathogens. Hence, cytokines used as the potential adjuvants have been studied increasingly 22 23 24 35 36 37 . IL-8 as a CXC chemokine produced by numerous cell types, was known to recruit neutrophils to inflammatory sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that co-vaccination of antigens with cytokines is a novel and effective strategy to enhance immunization and regulate cellular and humoral immune responses to promote protective immunity against pathogens. Hence, cytokines used as the potential adjuvants have been studied increasingly 22 23 24 35 36 37 . IL-8 as a CXC chemokine produced by numerous cell types, was known to recruit neutrophils to inflammatory sites.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are a family of low molecular weight and secretory proteins which involved in various pro-inflammatory functions against invasive pathogens including bacteria, virus or parasite. Chemokines as a kind of cytokines are among the adjuvants more widely used for vaccination against various pathogens in mammals 21 22 23 . To date, many cytokines and chemokines have been found in bony fish, and their functions and signaling are being explored with great progress 24 25 26 .…”
mentioning
confidence: 99%
“…Chemokines and chemokine receptors contribute to leukocyte trafficking and recruitment to sites of inflammation. Indeed, XCL1, CCL3 (MIP1α), CCL5 (RANTES), CCL7, CCL20, CCL21, CCL22, CCL25, CCL27, CCL28, CXCL10 and CXCL13 have been demonstrated to significantly promote cellular and humoral responses when fused or co-delivered with antigens from viruses or tumors [11][12][13][14][15][16][17]. However, systematic evaluation of the immune response of chemokines after fusing with antigens has not been reported.…”
Section: Introductionmentioning
confidence: 99%